Gastrodiplomasi Indonesia Melalui Wonderful Indonesia Di Sydney Periode 2017-2019 - Chelsea Canada (2020)
As time goes by, many countries begin to strengthen their soft power. Soft power is an effort to get something without using something coercive, but using the attraction that is owned by a country. In this case, the author will use culinary as Indonesia's attraction which is part of culture. Through this research, the author will discuss the implementation of Indonesia by carrying out gastrodiplomacy in Sydney through the Wonderful Indonesia as Indonesia's nation branding. This program is purposed in order to improve the visibility of Indonesia through culinary in Sydney, New South Wales and economic benefits. This research uses qualitative method and public diplomacy and gastrodiplomacy concept.